The Effect of Discovery Learning Assisted by PhET Simulation Media on Students’ Mathematics Learning Outcomes in Equivalent Fraction Material at SMP Negeri 2 Padangsidimpuan - Ramadhan Herianto; Almira Amir; Ahmad Nizar (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Mathematics learning requires instructional approaches that promote students' active participation and meaningful conceptual understanding. However, many junior secondary school students experience difficulties in learning equivalent fractions because the concepts are abstract and classroom instruction is often dominated by teacher-centered approaches with limited use of interactive learning media. This study aimed to examine the effect of the Discovery Learning model assisted by PhET Interactive Simulations on students' mathematics learning outcomes in equivalent fraction material. The study employed a quantitative approach using a quasi-experimental pretest–posttest control group design. Sixty seventh-grade students from SMP Negeri 2 Padangsidimpuan participated in the study and were divided into an experimental group and a control group. Data were collected using a validated mathematics achievement test and analyzed through descriptive statistics, the Kolmogorov–Smirnov normality test, Levene's homogeneity test, an Independent Samples t-test, N-Gain analysis, and the coefficient of determination using IBM SPSS Statistics. The results revealed that students who learned through Discovery Learning assisted by PhET Interactive Simulations achieved significantly higher mathematics learning outcomes than those who received conventional classroom instruction (p < 0.05). The experimental group also demonstrated greater learning improvement, as indicated by a higher N-Gain score, while the instructional treatment contributed 39.3% of the variance in students' learning outcomes. These findings indicate that integrating Discovery Learning with PhET Interactive Simulations provides an effective student-centered learning environment that enhances conceptual understanding and improves mathematics learning outcomes. Therefore, this instructional approach can be recommended as an alternative strategy for teaching equivalent fractions at the junior secondary school level.